1997
DOI: 10.1016/s0893-133x(96)00170-4
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Receptors in Suicide Victims with Major Depression

Abstract: Serotonin1A (5-HT1A) and serotonin2A (5-HT2A) receptors in the brain have been implicated in the pathophysiology of suicide. Brain samples were collected at autopsy from suicide victims with a current episode of major depression and matched comparison subjects who died of natural or accidental causes. Retrospective psychiatric assessments were collected from knowledgeable informants for all suicide victims and most of the comparison subjects. Psychiatric diagnoses were determined according to DSM-III-R criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 50 publications
5
91
2
1
Order By: Relevance
“…51 In contrast, most, but not all, studies in frontal cortex have reported no changes of postsynaptic 5-HT 1A serotonin receptors in depressed suicide victims. [52][53][54][55][56][57] The present study agrees with these data and demonstrates the unaltered functional status of these postsynaptic 5-HT 1A serotonin receptors in suicide victims with mood disorders. Recently, a widespread reduction in 5-HT 1A serotonin receptor binding potential has been drawn from positron emission tomography analysis of 25 depressed patients (unmedicated or medicated) with the selective antagonist [ 11 C]WAY-100635, 58 which could reflect either a reduction in the number of 5-HT 1A serotonin receptors or a decrease in receptor affinity.…”
Section: Molecular Psychiatrysupporting
confidence: 90%
“…51 In contrast, most, but not all, studies in frontal cortex have reported no changes of postsynaptic 5-HT 1A serotonin receptors in depressed suicide victims. [52][53][54][55][56][57] The present study agrees with these data and demonstrates the unaltered functional status of these postsynaptic 5-HT 1A serotonin receptors in suicide victims with mood disorders. Recently, a widespread reduction in 5-HT 1A serotonin receptor binding potential has been drawn from positron emission tomography analysis of 25 depressed patients (unmedicated or medicated) with the selective antagonist [ 11 C]WAY-100635, 58 which could reflect either a reduction in the number of 5-HT 1A serotonin receptors or a decrease in receptor affinity.…”
Section: Molecular Psychiatrysupporting
confidence: 90%
“…Second, downregulation of 5-HT 2A receptors is a common and reasonably specific characteristic for known antidepressant drugs (Peroutka and Snyder, 1980), although some controversy exists regarding the effects of SSRIs. Third, a trend exists for upregulation of 5-HT 2A receptor binding in discrete prefrontal cortical regions of suicide victims from postmortem studies (Pandey et al, 2002;Stockmeier et al, 1997). Fourth, blockade of 5-HT 2A receptors is one of the most common and potent shared pharmacological actions for a number of antidepressants (Marek et al, 1992) which do not appear to have antidepressant efficacy in patients due to blockade of SERT (serotonin transporters), NET (norepinephrine transporters), or monoamine oxidase (MAO; eg, mirtazapine, mianserin, nefazodone, trazodone, and iprindole).…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies concur, and several observe no difference in 5-HT 2A receptors in the prefrontal cortex in depressed suicides compared to controls. [35][36][37][38][39][40][41][42] In non-fatal suicide attempts, multiple platelet studies of 5-HT 2A receptors, serotonin reuptake sites, and serotonin second messenger systems have reported higher platelet 5-HT 2A receptor numbers in suicide attempters compared with nonattempters and healthy controls 43 , indications of impaired 5-HT 2A receptor mediated signal transduction in the prefrontal cortex of suicides 44 , and blunted 5-HT 2A receptor in major depression patients who made highlethality suicide attempts compared to those who made low-lethality suicide attempts. 45 The implications of such a defect in signal transduction, if present in the brain, would be that although there may be greater density of 5-HT 2A receptors, the signal which is transduced by 5-HT 2A receptor activation may be blunted, which would compound deficient serotonergic activity as seen in the lower levels of brainstem serotonin and/or 5-HIAA in suicide victims.…”
Section: Serotonin Receptorsmentioning
confidence: 99%